Efficacy of tenapanor hydrochloride for hyperphosphatemia in hemodialysis patients: a single-center retrospective observational study - Motohiro Okamura; Masatomo Yashiro; Tadashi Kamata; Hirohisa Kotera; Yasuhiko Okamura (Renal Replacement Therapy)
Abstract Background Well-controlled studies have reported the effective control of serum phosphorus levels (phosphorus) by tenapanor hydrochloride (tenapanor) in hemodialysis patients. Tenapanor has also been shown to reduce the phosphate binder (PB) pill burden. The present study investigated whether these effects occur in routine clinical practice. Methods The data of 94 patients collected until 31 July 2024 were examined. Information was obtained from electronic medical records before and after the initiation of tenapanor. Results A total of 29 patients had to discontinue tenapanor owing to diarrhea. The percentage of patients who habitually used laxatives was significantly higher in the continuation group than in the discontinuation group (32.3 versus 6.9%, p < 0.01). The average dose of tenapanor was 19.9 mg/day in the 65 patients who continued tenapanor. The observation period of these patients was 131.8 ± 14.5 days. A significant decrease was observed in phosphorus after the initiation of tenapanor (5.47 versus 4.84 mg/dL, p < 0.005). The achievement rate of phosphorus < 5.5 mg/dL significantly increased from 58.5% before the initiation of tenapanor to 76.9% after (p < 0.05). Following the exclusion of 4 patients who received an increased dose of PB, 19 of the remaining 61 patients were ultimately treated with tenapanor alone (monotherapy group). The ratio of phosphorus reduction was defined as follows: the value after the initiation of tenapanor was subtracted from the value before, and the result obtained was divided by the value before. This ratio was significantly higher in the combination therapy group than in the monotherapy group (0.127 versus −0.048, p < 0.005), while no significant difference was noted in the maintenance dose of tenapanor between the groups. A reduction of > 30% in the PB pill burden was achieved by 31 patients. Conclusions Diarrhea is the most clinically relevant side effect of tenapanor and resulted in its discontinuation in 31% of patients in this study. Tenapanor may reduce phosphorus, and this hypophosphatemic effect may be enhanced by its concomitant use with PB that lowers phosphate by a different mechanism from that of tenapanor. Tenapanor may also reduce the pill burden. The findings of well-controlled studies were confirmed in routine clinical practice.